2020
DOI: 10.3390/nu12082329
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Linoleic Acid Consumption on Lipid Risk Markers for Cardiovascular Disease in Healthy Individuals: A Review of Human Intervention Trials

Abstract: Cardiovascular disease (CVD) is the leading cause of death worldwide. Risk factors for developing this disease include high serum concentrations of total cholesterol, triglycerides, low-density lipoproteins, very-low density lipoproteins, and low concentrations of high-density lipoproteins. One proposed dietary strategy for decreasing risk factors involves replacing a portion of dietary saturated fatty acids with mono- and polyunsaturated fatty acids (PUFAs). The essential omega-6 PUFA, linoleic acid (LA), is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 104 publications
0
38
0
1
Order By: Relevance
“…It has been established that moderate LA intake, as a partial replacement for saturated fatty acids, reduces blood total cholesterol and low-density lipoprotein (LDL)-cholesterol concentrations [ 25 , 26 ]. This seems to be the result of the upregulation of hepatic LDL receptor (LDLR) gene and protein expression, thereby promoting hepatic clearance of circulating LDL [ 26 ]. LA enhances the transcription of the liver X receptor alpha (LXRα) gene, probably via peroxisome proliferator-activated receptors (PPARs).…”
Section: Omega-6 Pufas and Human Healthmentioning
confidence: 99%
“…It has been established that moderate LA intake, as a partial replacement for saturated fatty acids, reduces blood total cholesterol and low-density lipoprotein (LDL)-cholesterol concentrations [ 25 , 26 ]. This seems to be the result of the upregulation of hepatic LDL receptor (LDLR) gene and protein expression, thereby promoting hepatic clearance of circulating LDL [ 26 ]. LA enhances the transcription of the liver X receptor alpha (LXRα) gene, probably via peroxisome proliferator-activated receptors (PPARs).…”
Section: Omega-6 Pufas and Human Healthmentioning
confidence: 99%
“…It was observed that our brassica oil samples had very low levels of SFA (5.1–5.7%) and substantial amounts of MUFA (55.88–62%) and PUFA (31.54–36.91%). Due to their ability to reduce serum cholesterol and Low-Density Lipoprotein (LDL) levels, these genotypes may be used as good sources of essential fatty acids due to their high percentage of linoleic acid [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The linoleic acid level in corn oil is higher than that in peanut oil, canola oil, soybean oil, and olive oil. Triacylglycerol molecules of corn oil comprise 25% of Trilinolein (LLL) and 22% of 1,2‐Linolein‐3‐Olein (LLO) followed by 1,2‐Linolein‐3‐Palmitin (LLP) (15%), 1,2‐Oleoyl‐3‐Linolein (OOL) (11%), and 1‐Palmitin‐2‐Linolein‐3‐Olein (PLO) (10%) (Froyen & Burns‐Whitmore, 2020; Veljković et al., 2018; Wrigley et al, 2016). Also, the high levels of lutein and zeaxanthin and its average levels of tocopherols, tocotrienols, and phytosterols in corn kernel oil make it health beneficial by preventing macular degeneration (Moreau et al, 2007; Shende & Sidhu, 2015).…”
Section: Germ Oil Recovery and Qualitymentioning
confidence: 99%